DAMPAK WABAH PANDEMI COVID-19 TERHADAP INSENTIF PAJAK DI SEKTOR EKONOMI - Sari, Diah Permata; Adi, Estu Surya; Destiani, Firdha; Aryanto, Afrilianty Putri; Hidayati, Arianna; Afrina, Cassy; Agusni, Pratiwi Putri (Bussman Journal : Indonesian Journal of Business and Management, 2024)
The Covid-19 outbreak is very detrimental to many countries. Indonesia is no exception and has been hit by a very detrimental impact on this nation. Starting from 2020, all economic sectors will not immediately be affected, and the Indonesian population will also feel the devastating impact of this pandemic. The government does not just sit idly by watching this country's miserable situation, tax incentive policies are provided to taxpayers throughout Indonesia, this is one of the government's efforts to help this nation's economy remain strong. Providing economic stimulus to several sectors affected by the shock caused by this outbreak also provides a bit of fresh air. Then several research results indicate that the government's decision to implement tax incentives for economic actors has become a bit of a passion for economic actors in the Covid- 19 conditions. Using quantitative descriptive research methods with primary and secondary data analysis which is explained in detail and clearly in the description. The aim of this research is to find out how the government's policy on tax incentives affected the Indonesian economy during the Covid-19 pandemic. The basis for providing this tax incentive is the state's effort to implement the National Economic Recovery (PEN) program to stem the Indonesian economy which experienced a decline every time in 2020